A evolução das NR’s de segurança do trabalho no Brasil - Lemos, Ranna Raniely de Souza (Universidade Federal Rural do Semi-Árido, 2021)
Since 2019, two revisions have been made to the Regulatory Rule (NRs). The government's justification revolves around reducing bureaucracy, improving the country's economy and modernizing legislation. The biggest concern about the reformulations is the reduction of the worker's safety and health and, consequently, a numbers increase of work accidents in Brazil. This research presents the changes that occurred in the NRs from the year 2019 to the present. Several impacts generated by these changes that will also be studied. The methodology adopted for the elaboration of the work is based on consulation on research sites, monographs, scientific articles and works that address the subject. This paper presents the revisions that occurred in the Regulatory Rule in an objective and simple way, presenting the Rule before its update. In the stage of presentation of the Regulatory Rule, the text clearly addresses updates that occurred in annexes, paragraphs, items and sub-items, emphasizing the preserved rights of employees, rights and duties of employer and improvements brought to the government
Keywords: Normas Regulamentadoras; Atualização; Desburocratizar; Regulatory Rule; Update; Reduce bureaucracy; ENGENHARIAS::ENGENHARIA CIVIL